Peran Organisasi Profesi Pustakawan - Yusniah Yusniah; Sari Laily Rahmadani skb; Putrama Al-Chairi Pulungan; Chairani Nur Hidayah (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2023)
The librarian professional organization has an important role in carrying out the profession as a librarian. Librarians are basically tasked with managing the library properly and providing the best service for library visitors. This study aims to find out how the role of librarian professional organizations in improving the qualifications and competence of librarians. This study used a descriptive qualitative research method by presenting data related to research results in the form of words regarding the role of librarian professional organizations. The data collection technique used in this study was library research, namely collecting research data through extracting references based on literature studies obtained from books, articles, theses, and data that supports research. The conclusion that can be drawn from this study is that librarian professional organizations have a significant role in improving the quality of librarians. The role is to establish good cooperation with related parties that can help improve library performance.